Chapter 24 Before HIV Venereal disease among homosexually active men in England and North America - McKay, Richard A. (Routledge Histories, 2017)
The Routledge History of Disease draws on innovative scholarship in the history of medicine to explore the challenges involved in writing about health and disease throughout the past and across the globe, presenting a varied range of case studies and perspectives on the patterns, technologies and narratives of disease that can be identified in the past and that continue to influence our present. Organized thematically, chapters examine particular forms and conceptualizations of disease, covering subjects from leprosy in medieval Europe and cancer screening practices in twentieth-century USA to the ayurvedic tradition in ancient India and the pioneering studies of mental illness that took place in nineteenth-century Paris, as well as discussing the various sources and methods that can be used to understand the social and cultural contexts of disease. Chapter 24 of this book is freely available as a downloadable Open Access PDF under a Creative Commons Attribution-Non Commercial-No Derivatives 3.0 license. https://www.routledgehandbooks.com/doi/10.4324/9781315543420.ch24